The Platonizing Sethian Background of Plotinus's Mysticism - Mazur, Zeke, (Nag Hammadi and Manichaean Studies ;, 2021)
In The Platonizing Sethian Background of Plotinus's Mysticism , Zeke Mazur offers a radical reconceptualization of Plotinus with reference to Gnostic thought and praxis. A crucial element in the thought of the third-century CE philosopher Plotinus-his conception of mystical union with the One-cannot be understood solely within the conventional history of philosophy, or as the product of a unique, sui generis psychological propensity. This monograph demonstrates that Plotinus tacitly patterned his mystical ascent to the One on a type of visionary ascent ritual that is first attested in Gnostic sources. These sources include the Platonizing Sethian tractates Zostrianos (NHC VIII,1) and Allogenes (NHC XI,3) of which we have Coptic translations from Nag Hammadi and whose Greek Vorlagen were known to have been read in Plotinus's school.